Fluorescent Copper Nanomaterials for Sensing NO2− and Temperature - Wang, Ning; Ga, Lu; Ai, Jun; Wang, Yong (Frontiers in Chemistry, 2022)
In this work, high fluorescent copper nanomaterials were synthesized by using ascorbic acid as ligand. Nitrite can selectively quench the fluorescence of copper nanomaterials. There is a good linear relationship between the quenching fluorescence intensity and nitrite concentration in the range of 10 μM - 180 μM. The correlation coefficient was 0.9435. Therefore, copper nanomaterials can be used to selectively detect nitrite ions. At the same time, we found that the fluorescence intensity of copper nanomaterials has a good correlation with the temperature (20-60 ℃), which shows great potential in the application of nano thermometers.